Work, life, and the gender effect: Perspectives of ACVIM Diplomates in 2017. Part 2—The intersection of personal life and professional career. (19th August 2020) - Morello, Samantha L.; Colopy, Sara A.; Chun, Ruthanne; Buhr, Kevin A.
Abstract: Background: In the field of veterinary surgery, women neither marry nor have children at the same rate as men, and those who do may experience more career disruption as a result. The American College of Veterinary Internal Medicine (ACVIM) is 1 of the few areas of specialized medicine that is predominantly female; it is unknown if such a demographic shift would produce a different environment for individuals cultivating their personal life. Hypothesis/Objectives: To report data regarding subjective and objective aspects of the intersection of the personal and professional lives of Diplomates of the ACVIM. Sample: Eight hundred ninety‐six surveys (781 completed) of ACVIM Diplomates, including cardiology, large and small animal internal medicine, neurology, and oncology. Methods: An 82‐item online survey was distributed to ACVIM Diplomates via Diplomate college listservs. Participation was voluntary. Results: Men were more likely to be married and have children than were women. Women had or adopted their first child at a later career stage compared with men, and agreed more strongly that career stage was an influential factor in family planning. Those with children worked fewer hours compared with those without, and this effect was greater among women. Women were more likely to require external childcare, but most men and women shared childcare responsibilities equally outside of working hours. Conclusions and Clinical Importance: The intersection of personal and professional life differs between men and women in the ACVIM, which may create different needs, preferences, or barriers to work‐life balance in the workforce.